Roles of Specialized Pro-Resolving Lipid Mediators in Cerebral Ischemia Reperfusion Injury - Yin, Ping; Wei, Yafen; Wang, Xu; Zhu, Mingqin; Feng, Jiachun (Frontiers in Neurology, 2018)
Ischemic stroke contributes to approximately 80% of all stroke cases. Recanalization with thrombolysis or endovascular thrombectomy are currently critical therapeutic strategies for rebuilding the blood supply following ischemic stroke. However, recanalization is often accompanied by cerebral ischemia reperfusion injury that is mediated by oxidative stress and inflammation. Resolution of inflammation belongs to the end stage of inflammation where inflammation is terminated and the repair of damaged tissue is started. Resolution of inflammation is mediated by a group of newly discovered lipid mediators called specialized pro-resolving lipid mediators (SPMs). Accumulating evidence suggests that SPMs decrease leukocyte infiltration, enhance efferocytosis, reduce local neuronal injury, and decrease both oxidative stress and the production of inflammatory cytokines in various in vitro and in vivo models of ischemic stroke. In this review, we summarize the mechanisms of reperfusion injury and the various roles of SPMs in stroke therapy.